Pole leksykalno-semantyczne nazw kolorów jako obiekt przekładu (na przykładzie utworu „Pan Tadeusz” Adama Mickiewicza i jego tłumaczenia na język rosyjski Światosława Świackiego) - Goszczyńska, Aleksandra (Kultury Wschodniosłowiańskie – Oblicza i Dialog, 2018)
The present article analyzes the translation of the lexical and semantical field of color-naming (on the basis of Adam Mickiewicz’s Pan Tadeusz and its Russian translation by Światosław Świacki). The analysis focuses on the contexts in which the words denoting the semantics of colors function. The lexical and semantic field of color-naming has been characterized and divided into sub-fields (representatives sub-fields for chromatic and achromatic colors have been distiguished as well as the color-naming words have been divided according parts of speech). The main part of the paper is devoted to the analysis of translating tools used by Światosław Świacki in order to refelct the semantics of colors in the translation.